2010
DOI: 10.1016/j.bbamem.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

RNA and DNA interactions with zwitterionic and charged lipid membranes — A DSC and QCM-D study

Abstract: The aim of the present study is to establish under which conditions tRNA associates with phospholipid bilayers, and to explore how this interaction influences the lipid bilayer. For this purpose we have studied the association of tRNA or DNA of different sizes and degrees of base pairing with a set of model membrane systems with varying charge densities, composed of zwitterionic phosphatidylcholines (PC) in mixtures with anionic phosphatidylserine (PS) or cationic dioctadecyl-dimethyl-ammoniumbromide (DODAB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 77 publications
5
65
0
Order By: Relevance
“…These observations also raise questions as to whether lncRNAs can recruit adaptor proteins such as GRB2 to the vicinity of the carboxy-termini of membrane-bound receptors containing SH2 domains, which are responsible for the direct modulation of RTK-mediated cell signaling cascades. These observations also support an earlier hypothesis from studies on RNA viruses, concerning RNA-lipid interactions, specifically those with charged moieties including phosphatidylcholine (PC) and phosphatidylserine (PS), are crucial in supporting life [99][100][101][102] . Further work is warranted to elucidate the complexities of these lncRNAs that operate as trans regulators of cell signaling pathways.…”
Section: Lncrnas Modulate Cell Signaling Pathwayssupporting
confidence: 87%
“…These observations also raise questions as to whether lncRNAs can recruit adaptor proteins such as GRB2 to the vicinity of the carboxy-termini of membrane-bound receptors containing SH2 domains, which are responsible for the direct modulation of RTK-mediated cell signaling cascades. These observations also support an earlier hypothesis from studies on RNA viruses, concerning RNA-lipid interactions, specifically those with charged moieties including phosphatidylcholine (PC) and phosphatidylserine (PS), are crucial in supporting life [99][100][101][102] . Further work is warranted to elucidate the complexities of these lncRNAs that operate as trans regulators of cell signaling pathways.…”
Section: Lncrnas Modulate Cell Signaling Pathwayssupporting
confidence: 87%
“…The formation of equilibrium clusters composed of positively charged liposomes stuck together by a polyanionic polyacrylate was demonstrated [45]. The adsorption of tRNA on the surface of lipid bilayers can lead to segregation in the mixed anionic or cationic bilayers, where tRNA is likely excluded from the anionic-rich domains in the first system, and associated with the cationic-rich domains in the second system [46]. Conditions such as the lipid composition of liposomes and salt concentration, under which DNA is still physically associated with positively charged liposomes, were previously studied [47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sphingomyelin (SM) binds RNA and prevents its degradation by RNAses [139,140]. Moreover, a few groups have reported that small RNAs could bind to phospholipid membranes using vesicular models [141][142][143][144]. Whether the plasma membrane SM, enriched into lipid rafts, could also bind miRNA and contribute to its export to HDLs has not been published so far.…”
Section: Mirna Transfer To Hdlsmentioning
confidence: 99%